Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T19:58:25+01:00
A)-2a+b-a-2b+3a
-2a-a+3a+b-2b
-3a+3a-1b
-1b

b)-ab+b²+3ab-2ab
-ab+3ab-2ab+b²
3ab-ab-2ab-b²
3ab-3ab-b²
-b²

c)⅔x+⅓y+2⅓x-⅓y
⅔x + 2⅓x + ⅓y -⅓y
3x

d)15xy-4x+8y-6xy+5x-xy
-4x+5x+8y+15xy-6xy-xy
x+8y+15xy-7xy
x+8y+8xy

2010-03-02T20:00:08+01:00
A)-2a+b-a-2b+3a = -b
b)-ab+b²+3ab-2ab = b²
c)⅔x+⅓y+2⅓x-⅓y = 3x
d)15xy-4x+8y-6xy+5x-xy=8xy+x+8y
e)o,2x²-2y+1,8x²+4,3y-x=2x²+2,3y
f)-¼m+⅛n-⅛m+0,375m=0 wszystko sie odrazu zredukowalo
2010-03-02T20:06:21+01:00
A)-2a+b-a-2b+3a=2a+b
b)-ab+b²+3ab-2ab=-6ab-b²
c)⅔x+⅓y+2⅓x-⅓y=1/3y
d)15xy-4x+8y-6xy+5x-xy=8xy-9x-8y
e)o,2x²-2y+1,8x²+4,3y-x=1,6x²-6,3y
f)-¼m+⅛n-⅛m+0,375m=0,125n